1967
DOI: 10.2307/4593102
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Rheumatic Fever in Metropolitan Nashville, 1963-65

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

1969
1969
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…As expected, studies using active surveillance methods exhibited relatively higher incidence rates, which ranged from 8 to 51/100 000 (median 22; interquartile range 10–23/100 000), compared with those employing passive surveillance with lower incidence rates of 5–35/100 000 (median 16; interquartile range 5–18/100 000). Crude incidence rates and age-adjusted rates derived from studies from the USA,12 Chile,13 Martinique and Gouadaloupe,14 and Sweden16 showed a low ARF incidence of ⩽10/100 000 per year; while those from Eastern Europe,15 Middle East,17 – 19 Asia,20 and Australasia21 had a higher incidence >10/100 000 per year. Six of the 10 included studies assessed the incidence of ARF in the first three decades of life,16182021 and the remainder included all age groups 1214 19.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…As expected, studies using active surveillance methods exhibited relatively higher incidence rates, which ranged from 8 to 51/100 000 (median 22; interquartile range 10–23/100 000), compared with those employing passive surveillance with lower incidence rates of 5–35/100 000 (median 16; interquartile range 5–18/100 000). Crude incidence rates and age-adjusted rates derived from studies from the USA,12 Chile,13 Martinique and Gouadaloupe,14 and Sweden16 showed a low ARF incidence of ⩽10/100 000 per year; while those from Eastern Europe,15 Middle East,17 – 19 Asia,20 and Australasia21 had a higher incidence >10/100 000 per year. Six of the 10 included studies assessed the incidence of ARF in the first three decades of life,16182021 and the remainder included all age groups 1214 19.…”
Section: Resultsmentioning
confidence: 97%
“…Crude incidence rates and age-adjusted rates derived from studies from the USA,12 Chile,13 Martinique and Gouadaloupe,14 and Sweden16 showed a low ARF incidence of ⩽10/100 000 per year; while those from Eastern Europe,15 Middle East,17 – 19 Asia,20 and Australasia21 had a higher incidence >10/100 000 per year. Six of the 10 included studies assessed the incidence of ARF in the first three decades of life,16182021 and the remainder included all age groups 1214 19. In two studies, the incidence per year of age could be obtained,15 16 and in one study the childhood and adult incidence measures could be analysed separately 15.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations